Ex vivo γH2AX radiation sensitivity assay in prostate cancer: Inter-patient and intra-patient heterogeneity - De-Colle, Chiara; Yaromina, Ala; Hennenlotter, Joerg; Thames, Howard; Mueller, Arndt-Christian; Neumann, Tim; Stenzl, Arnulf; Scharpf, Marcus; Fend, Falko; Ricardi, Umberto; Baumann, Michael; Zips, Daniel; et al. (Radiotherapy and oncology, 2017)
The aim of the study is to assess inter-patient and intra-patient heterogeneity in tumour cell radiosensitivity using the ex vivo γH2AX assay in prostate cancer specimens. Excised specimens from untreated prostate cancer patients were cultivated 24h in media, irradiated ex vivo and fixed after 24h. Residual γH2AX foci were counted and the slope of the dose response was calculated. Intra-patient heterogeneity was studied from three to seven different biopsies. In pathology-confirmed tumour samples from 21 patients the slope of residual γH2AX foci and radiation dose showed a substantial heterogeneity ranging from 0.82 to 3.17 foci/Gy. No correlation was observed between the slope values and the Gleason score (p=0.37), prostate specific antigen (p=0.48) and tumour stage (p=0.89). ANOVA indicated that only in 1 out of 9 patients, biopsies from different tumour locations yielded statistically significant differences. Variance component analysis indicated higher inter-patient than intra-patient variability. Bootstrap simulation study demonstrated that one biopsy is sufficient to estimate the mean value of residual γH2AX per dose level and account for intra-patient heterogeneity. In prostate cancer inter-patient heterogeneity in tumour cell radiation sensitivity is pronounced and higher than intra-patient heterogeneity supporting the further development of the γH2AX ex vivo assay as a biomarker for individualized treatment.